Transparenz und Forward Guidance: Stimulierung der Volkswirtschaft in der Eurozone? - Ansgar Belke (Wirtschaftsdienst, 2014)
Das Kommunikationsverhalten der EZB wird verschiedentlich kritisiert. Zwei Instrumente, 'mehr Transparenz' und 'Forward Guidance', stehen dabei im Mittelpunkt. Die Veröffentlichung von Protokollen der EZB-Ratssitzungen wird immer wieder angemahnt, und die EZB gibt mittlerweile eine Vorausschau auf die langfristig geplante Zinsentwicklung. Vor der Krise lag die EZB im Transparenz-Ranking weit vorn, die Bekämpfung der Krise hat allerdings eine größere Geheimhaltung erforderlich gemacht. Tatsächlich wird die Geldpolitik der EZB durch die neuen Kommunikationsinstrumente berechenbarer und kann entsprechend leichter zur Rechenschaft gezogen werden. – – The author delivers details on whether and how the effectiveness of the ECB's policies can be improved through more transparency and 'forward guidance'. Is publishing the minutes of Council meetings really a good idea? How should we assess the publication of the details of who has voted (and in what way) in the meetings? Is the ECB plagued by deficiencies in transparency, with an eye on the bank's steadily growing responsibilities? Should the ECB stick to the instrument of 'forward guidance' even beyond the crisis period? How predictable and assessable can and must monetary policy be? Can central banks endowed with too much guidance become a source of volatility? The ECB will adopt banking surveillance in the euro area: do particular transparency and accountability obligations result from this? And if yes, how can they be fulfilled? Finally, the author assesses the limits of the transparency and communication of central banks.
Keywords: E52; E58; E61; 330